Improvement of HEK293 Cell Growth by Adapting Hydrodynamic Stress and Predicting Cell Aggregate Size Distribution - Stefan Seidel; Rüdiger W. Maschke; Fruhar Mozaffari; Regine Eibl-Schindler; Dieter Eibl (Bioengineering, 2023)
HEK293 is a widely used cell line in the fields of research and industry. It is assumed that these cells are sensitive to hydrodynamic stress. The aim of this research was to use particle image velocimetry validated computational fluid dynamics (CFD) to determine the hydrodynamic stress in both shake flasks, with and without baffles, and in stirred Minifors 2 bioreactors to evaluate its effect on the growth and aggregate size distribution of HEK293 suspension cells. The HEK FreeStyleTM 293-F cell line was cultivated in batch mode at different specific power inputs (from 63 <semantics>W m−3</semantics> to 451 <semantics>W m−3</semantics>), whereby <semantics>≈60 W m−3</semantics> corresponds to the upper limit, which is what has been typically described in published experiments. In addition to the specific growth rate and maximum viable cell density VCD<semantics>max</semantics>, the cell size distribution over time and cluster size distribution were investigated. The VCD<semantics>max</semantics> of <semantics>(5.77±0.02)·106</semantics><semantics>cells</semantics><semantics>m</semantics><semantics>L−1</semantics> was reached at a specific power input of 233 <semantics>W m−3</semantics> and was <semantics>23.8%</semantics> higher than the value obtained at 63 <semantics>W m−3</semantics> and <semantics>7.2%</semantics> higher than the value obtained at 451 <semantics>W m−3</semantics>. No significant change in the cell size distribution could be measured in the investigated range. It was shown that the cell cluster size distribution follows a strict geometric distribution whose free parameter p is linearly dependent on the mean Kolmogorov length scale. Based on the performed experiments, it has been shown that by using CFD-characterised bioreactors, the VCD<semantics>max</semantics> can be increased and the cell aggregate rate can be precisely controlled.